Modeling microbe-host interaction in the pathogenesis of Crohn’s disease - Mohamed Ahmed; Amira Metwaly; Dirk Haller (International Journal of Medical Microbiology, 2021)
Alterations in the gut microbiota structure and function are thought to play an important role in the pathogenesis of Crohn’s disease (CD). The rapid advancement of high-throughput sequencing technologies led to the identification of microbiome risk signatures associated with distinct disease phenotypes and progressing disease entities. Functional validation of the identified microbiome signatures is essential to understand the underlying mechanisms of microbe-host interactions. Germfree mouse models are available to study the functional role of disease-conditioning complex gut microbial ecosystems (dysbiosis) or pathobionts (single bacteria) in the pathogenesis of CD-like inflammation. Here, we discuss the clinical and mechanistic relevance and limitations of gnotobiotic mouse models in the context of CD. In addition, we will address the role of diet as an essential external factor modulating microbiome changes, potentially underlying disease initiation and development.